Pengaruh Suhu dan Lama Pengeringan Terhadap Beberapa Mutu Manisan Belimbing Wuluh (Averrhoa bilimbi L.) Kering - Shanti Fitriani (Universitas Riau, 2008)
The effect different drying temperatures (75, 80, 85 and 90ºC) and drying times (12, 13, 14 dan 15 hours) on the production of dried sweetened belimbing wuluh was evaluated. Data obtained by thzndicate that different drying temperature and drying time significantly affected the water content and solid total, however no effect of these compounds on sucrose content. Combination of 90ºCof drying temperature and 14 hours of drying time exhibited the lowest water content and highest solid total that met the SNI dried sweetened.